Escolarização de jovens do ensino noturno da Escola do Lombo-Lombo (Cabinda - Angola, 1990-2013) - Selpa Pemba Tomas Buza (2014)
The goal ofthis dissertation is to analyze evening school education of youngsters on site in public schools from Cabinda, Angola, more specifically in Lombo-Lombo School in the 1990-2013 time frame. Based on the hypothesis that in addition to education, evening students also seek out equality of opportunities and forms of non-exclusion, we conducted field work to learn about their desires while attending school. To conduct this study, we investigated the history of education in Angola, the policy of implementation ofthe recovery program for youngsters lagging behind in their education, the Andragogy pedagogical approach, the organization of the Lombo-Lombo School and the operation of evening classes. Empirical data were collected by oral history methodology through interviews and questionnaires applied to school directors, teachers, students' relatives and the students themselves. Documents such as legislation and Lombo-Lombo School archives were also analyzed. The collected data allowed for the profiling of the educational policy for youngsters for the recovery of schooling delay in public schools in the province of Cabinda. We concluded that young and adult students attend school seeking an opportunity of a better future, that is, because of their aspirations in lifeand their belief that education will serve as a means to fulfill such aspirations.